Comparison of Extenders With the Addition of Egg Yolk for Cooling Alpaca Sperm Obtained From Deferent Ducts - Bertuzzi, Mariana Lucía; Torres, Edita Yola; Huanca, Teodosio; Neild, Deborah; Carretero, María Ignacia (Frontiers in Veterinary Science, 2020)
The use of non-commercial and commercial extenders for cooling alpaca sperm has already been reported, the latter showing certain advantages over the first. The Andromed® (AM) extender was created for use in ruminants and has also been tested in ejaculated and epididymal alpaca sperm. According to the manufacturer, this extender does not need the addition of egg yolk (EY); however, it is known that the addition of EY to some extenders improves the preservation of cooled sperm. The objective of this study therefore was to compare a non-commercial extender (Tris) with the addition of EY versus the commercial extender AM with and without the addition of EY, for cooling alpaca sperm obtained from diverted deferent ducts. Fifteen pools of deferent duct sperm were formed using samples from two or three different males for each. Each sperm pool was evaluated and then divided into three aliquots that were diluted to a final concentration of 30x106 sperm ml-1 (0 h) with either: 1) Tris with 20% EY (T-EY), 2) AM or 3) AM with 20% EY (AM-EY). Samples were cooled to 5 °C and the following sperm parameters were evaluated after 24 and 48 h of storage: motility, viability, membrane function, acrosome integrity, morphology and chromatin condensation. Motility was also evaluated after 72 h of storage. The samples that best preserved progressive and total sperm motility at the 24 and 48 h evaluation periods were the ones diluted with AM-EY, observing that with this extender these motility patterns decreased significantly after 72 h of storage compared to time 0 h (p<0.05). A significant decrease (p<0.05) in total and progressive motility was observed at 48 h for the T-EY and AM extender compared to 0 h. AM was the only extender in which the percentages of viable sperm decreased significantly (p<0.05) after 48 h of conservation. For the rest of sperm parameters evaluated, no significant differences were observed between any of the extenders at any evaluation time. The Andromed® extender with the addition of 20% EY could be an alternative option for cooling alpaca sperm obtained from deferent ducts.